2015
DOI: 10.1111/sms.12630
|View full text |Cite
|
Sign up to set email alerts
|

Association of sedentary time and physical activity with pain, fatigue, and impact of fibromyalgia: the al‐Ándalus study

Abstract: We examined the association of objectively measured sedentary time (ST) and physical activity (PA) levels with pain, fatigue, and the impact of the disease in women with fibromyalgia. Four hundred and nineteen (mean age ± SD = 51.7 ± 7.6 years old) women with fibromyalgia participated. ST and PA levels (light, moderate, and moderate-to-vigorous [MVPA]) were measured with triaxial accelerometry. We assessed experimental pain with algometry and clinical pain, fatigue, and impact of fibromyalgia with a number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
67
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(78 citation statements)
references
References 41 publications
9
67
2
Order By: Relevance
“…The symptoms found and the impact of FM were similar to reports in other qualitative studies (ie, Cunningham & Jillings, ; Hallberg & Carlsson, ; Sturge‐Jacobs, ). However, recent studies have shown that lower levels of physical inactivity are associated with lower pain, fatigue and impact of disease (Segura‐Jiménez et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The symptoms found and the impact of FM were similar to reports in other qualitative studies (ie, Cunningham & Jillings, ; Hallberg & Carlsson, ; Sturge‐Jacobs, ). However, recent studies have shown that lower levels of physical inactivity are associated with lower pain, fatigue and impact of disease (Segura‐Jiménez et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The high dropout rate is mainly related to general ill‐health rather than to worsening of FM symptoms related to participation in the PA program . In this regard, sedentary time is independently and positively associated with levels of pain, fatigue, and impact of the disease in women with FM . When sedentary time is substituted with light PA, better bodily pain, social function, vitality, and disease impact are observed …”
Section: Introductionmentioning
confidence: 99%
“…Sedentary time, PA, and SQ appear to be interconnected and all of them are related to the quality of life . Lower ST or higher PA levels are associated with reduced general symptomatology in patients with fibromyalgia . However, little is known about the contribution of ST and PA intensity levels on SQ in women with fibromyalgia.…”
Section: Introductionmentioning
confidence: 99%
“…23 Lower ST or higher PA levels are associated with reduced general symptomatology in patients with fibromyalgia. 24 However, little is known about the contribution of ST and PA intensity levels on SQ in women with fibromyalgia. Therefore, the aims of the present study were (a) to examine the association of objectively measured ST and PA intensity levels with SQ in women with fibromyalgia and (b) to assess whether those who meet moderate-to-vigorous physical activity (MVPA) recommendations have better SQ than their counterparts.…”
Section: Introductionmentioning
confidence: 99%